Effects of continuous and released compressive force on osteoclastogenesis in vitro - Boontida Changkhaokham; Sumit Suamphan; Suwanna Jitpukdeebodintra; Chidchanok Leethanakul (Elsevier, 2024)
Objective: Compressive force has been found to be catabolic to alveolar bone during orthodontic tooth movement. This study quantified the fusion of mononuclear RAW 264.7 cells (a murine osteoclastic-like cell line) into multinucleated osteoclasts under a hydrostatic pressure-generated mechanical compression-the new model of various magnitudes and durations. Methods: RAW 264.7 cells were subjected to 0.3, 0.6 or 0.9 g/cm2 of compressive force by an acrylic cylinder custom-made by laser cutting or no compressive force for 4 days during osteoclastogenic induction. TRAP-positive multinucleated cells were quantified. For the release from force experiment, osteoclastogenesis was induced by 0.6 g/cm2 mechanical stimuli for 0, 1, 2, 3 or 4 days. Cell viability, TRAP-positive multinucleated cells, DCSTAMP and Cathepsin K (CTSK) gene expression were evaluated 4 days after release from force. Results: Compressive force at 0.6 and 0.9 g/cm2 significantly increase the number of TRAP-positive multinucleated cells (P < 0.05). Release from continuous mechanical compression after 4 days significantly elevated the number of TRAP-positive multinucleated cells and DCSTAMP and CTSK mRNA expression, with no adverse effects on cell viability (P < 0.05). Conclusions: Continuous stimulation with compressive force induced osteoclastogenesis in RAW 264.7 cells by enhancing DCSTAMP and CTSK expression, which provides new understanding of bone remodeling during orthodontic treatment.